Prevalensi Infeksi Cacing Trichuris spp. Pada Sapi Bali Berdasarkan Letak Geografis Provinsi Bali (THE PREVALENCE OF TrichurisSpp IN BALI CATTLE ACCORDING TO THE LAYOUT GEOGRAPHIC OF BALI PROVINCE) - Pramasudha, Anak Agung Raka; Suratma, Nyoman Adi; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2015)
The purposes of this study were to determine the prevalence of Trichuris spp. on bali cattle(Bos sondaicus) and the relationship between the prevalence with the geographical location in Bali. The samples that used in this study were 200 fecal samples from four different geographicallocation in Bali.  The study was a cross-sectional study to determine the prevalence of Trichurisspp. on bali cattle (Bos sondaicus) with geographic location as a risk factor.  The examination was done using floating in saturated salt solution method. Identification of Trichuris spp. based onmorphology eggs was done with 40x magnificence under a binocular microscope.  While therelationship between geographic location and the prevalence of Trichuris spp. was analyzed byusing Chi square test.  The results showed that the prevalence of Trichuris spp. on bali cattle was1,5%, and there was no relation between geographic location and the prevalence of Trichuris spp.
Keywords: bali cattle; geography; prevalence; Trichuris spp